TRADISI MEGALITIK DAN DINAMIKA KEAGAMAAN DI PULAU TERNATE TIDORE (MAKNA PADA MASYARAKAT PENDUKUNGNYA) - Nurachman Iriyanto (Lembaga Penelitian Universitas Trisakti, 2018)
Megalithic tradition is an ongoing and well-maintained cultural fact to date. The megalithic tradition is not simply about large stones; rather it‟s about the